Student Reading Skills Improvement Through Dyslexia Reading Procedures - Mazlinah binti Abd Mutalib (Best Practices in Disability-Inclusive Education, 2022)
By using a window ruler, this best practice aims to improve dyslexic students' reading skills based on the reading module. Reading is a complex activity that involves both physical and mental activities. Reading activities are also linked to eye movements and visual acuity. Reading methods based on the Dyslexia Reading Procedure can help students improve their reading skills and reduce syllable, word, and sentence reading errors without skipping lines. This practice involves four Sakura dyslexic students from SMK Padang Temu Melaka (Padang Temu Secondary School) in a report and observation format. The use of this best practice implies that teachers can use the Dyslexia Reading Procedure during teaching sessions by using teaching aids. It is hoped that this best practice will help boost the confidence and motivation of special education students, particularly dyslexic students, as well as make the teaching and facilitation process (PdPc) more enjoyable to implement.